Nutrition of the intervertebral disc: solute transport and metabolism. - Holm, S; Maroudas, A; Urban, J; Selstam, G; Nachemson, A (Informa Healthcare, 1981)
The metabolism of the canine nucleus pulposus was investigated at different oxygen tensions. It was found that even at high oxygen tensions the metabolism is mainly anaerobic, only approximately 1.5% of the glucose being converted to carbon dioxide. The concentration dependence of oxygen consumption is limited to very low oxygen tensions. Values of oxygen consumption and lactic acid production were used to calculate the concentration profiles of these substances within the nucleus pulposus, using a diffusion theory. The predicted concentration profiles were compared with the experimental measurements of concentration at various positions in the disc. The good agreement in these values found in the nucleus confirms that the main mechanism of metabolite transport is diffusion, and the main route of nutrient supply into the nucleus is via the endplate.